Situating the social sciences in responsible innovation in the global south: the case of gene drive mosquitoes - Katie Ledingham; Chris Opesen; Sarah Hartley; Stella Neema (Journal of Responsible Innovation, 2023)
ABSTRACTThere has been growing attention in recent years on the potential reconfiguration of responsible innovation (RI) to increase its relevance for global challenges in the Global South. This reconfiguration will require a broad and empowered role for social scientists. Yet RI has been preoccupied with public and stakeholder inclusion, rather than social science inclusion. We probe this gap through a case study of the social sciences in the development of gene drive mosquitoes for malaria control in Mali and Uganda. Our data reveals potential diverse roles and future research agendas for the social sciences. We outline some challenges facing the social sciences in this space and ways to promote and support them. Lastly, we argue that RI’s predilection for reflexive and critical social science obscures a richer repertoire of social science roles that are an imperative and fundamental part of efforts to address global challenges in the Global South.